Fisheries disputes in Latin America - Andrade, Roberto de (UN. ECLAC SantiagoCL, 1999)
Reviews the most recent fisheries disputes which have affected the region. Identifies their causes and analyses their economic implications for the countries concerned and the means available for dispute settlement, as well as the policies to be adopted in order to avoid such confrontations, which can slow sectoral investment and the growth of the Latin American economies.